Faktor-Faktor Yang Mempengaruhi Kinerja Pegawai Negeri Sipil Pada Kantor Balai Pendidikan Dan Pelatihan Kehutanan Kupang - Upik Djaniar; Abdul Malik Hasyim; Vera Herlina Mustari (Program Studi Manajemen - Fakultas Ekonomi - Universitas Muhammadiyah Kupang, 2019)
This study aims to analyze the effect of discipline, skills, workenvironment and work facilities simultaneously and partially on theperformance of civil servants at the Kupang Forestry Education andTraining Center. The research sample was 56 people. The samplingtechnique uses saturated samples. The main instrument used in datacollection is a questionnaire. Data were analyzed using multipleregression analysis techniques. The analysis shows that simultaneousdiscipline, skills, work environment and work facilities have asignificant effect on performance. Discipline, skills, work environmentand work facilities also have a significant effect on performance.